PELATIHAN PROSEDUR LABORATORIUM ANALISIS DNA - Dewi Indriyani Roslim; Herman Herman; Roza Elvyra; Nery Sofiyanti; Ennie Chahyadi (LPPM UMRI, 2018)
Currently, analysis based on DNA is one of the techniques for solving the problems such as paternity test, determining the identity of accident victims, natural disasters victims, and authentication of foods ingredients. But not everyone knows about the stages of DNA analysis laboratory procedures. The purpose of this workshop is to provide knowledgments about DNA analysis laboratory procedures. The training was attended by 30 participants from various universities and research centers in Riau Province. Workshop materials include DNA isolation of animal, plant and bacterial, electrophoresis, polymerase chain reaction (PCR), and visualization of DNA bands. Evaluation uses a questionnaire distributed to participants. Questionnaire analysis showed that workshop was very useful especially for beginners who want to be involved in DNA analysis activities in the laboratory.